Effect of surfactant HLB on some gel properties of pigeonpea and cowpea starches - Mwasaru, Mwanjala A.; Muhammad, Kharidah (Wiley, 2001)
The pasting profiles, load penetration responses, and freeze-thaw stability of pigeonpea and cowpea starches were investigated as a function of hydrophilic-lipophilic balance (HLB) of surfactants. Incorporation of surfactants varying in HLB values resulted in significant (p< 0.05) increases in the initial pasting temperature of the starch pastes; the magnitude of the increment was concomitant with increases in HLB values. Surfactants of HLB 1.8, 3.8, 6.7, 16.0, and 20.0 significantly decreased the paste consistency of pigeonpea starch pastes at 97 °C. The cowpea starch paste consistencies at the same temperature was reduced by surfactants of HLB 16 and 20. Gel strength, elastic modulus and stickiness of the starch gels were significantly reduced by addition of surfactants. However, no clear-cut trends between surfactant HLB and these gel characteristics were apparent. Cowpea starch gels incorporating surfactants with HLB 1.8-11.0 exhibited significant improvement in freeze-thaw stability relative to the control but the stability of pigeonpea gels decreased. Addition of hydrophilic surfactants (HLB 16 and 20) invariably caused a significant increase in net syneresis of the starch gels. It was concluded that the pasting and rheological properties of cowpea and pigeonpea starches could be manipulated, in the short term, by varying the HLB values of added surfactants.